The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/agriculture8080119
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous Emissions after Soil Application of Pellet Made from Composted Pig Slurry Solid Fraction: Effect of Application Method and Pellet Diameter

Abstract: The study aimed at determining ammonia and GHG emissions from soil fertilized with pellets made from composted pig slurry solid fraction and to evaluate the effects of pellet diameter and pellet application method on gaseous emissions. A laboratory scale experiment was carried out investigating two composts: pig slurry solid fraction compost (SSFC) and pig slurry solid fraction mixed with wood chips compost (WCC). The two composts were pelettized in two different diameters—6 and 8 mm—by means of mechanical pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Furthermore, these results are in the range reported by Pampuro et al [30,33], who found N 2 O emissions of about 30-240 g N 2 O-N ha −1 at a fertilizer level of 200 kg N ha −1 . Although the period of measurements in their work was considerably longer, most emissions were also registered during the first week after application [30,33].…”
Section: Study Implications Related To Pellet Application In the Fieldsupporting
confidence: 85%
See 2 more Smart Citations
“…Furthermore, these results are in the range reported by Pampuro et al [30,33], who found N 2 O emissions of about 30-240 g N 2 O-N ha −1 at a fertilizer level of 200 kg N ha −1 . Although the period of measurements in their work was considerably longer, most emissions were also registered during the first week after application [30,33].…”
Section: Study Implications Related To Pellet Application In the Fieldsupporting
confidence: 85%
“…Within a measuring period of one month, Cabrera et al [31,32] reported nitrous oxide (N 2 O) emissions from soils after pellet utilization between 0.2 and 3.9% of applied N. The N 2 O flux rates depended on the soil water regime and on physical characteristics of the pellets. Pampuro et al [33] measured N 2 O emissions between 0.05 and 0.12% of applied N, depending on pellet size and application method. For CH 4 and NH 3 , negligible release was reported [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few data available on farm-composting in Europe, despite this technology has the advantage of saving transport costs and reducing emissions [47]. Conversely, there are different studies on composting processes for animal wastes and their GHG emissions, especially after soil application of these materials [38,57]. The amount of CO 2 emissions associated to the composting process (excluding the materials collection phase) were comparable with the values in Pergola et al [45].…”
Section: Environmental Sustainability Assessmentmentioning
confidence: 69%
“…Previous studies (e.g., [13,[16][17][18][19][20][21][22][23][24]) mainly focused on the effect of feedstocks in combination with management practices. However, no evaluation of the single steps within an entire processing chain could be found.…”
Section: Introductionmentioning
confidence: 99%